Synthesis of PEGylated alternating copolymer bearing thioether pendants for oxidation responsive drug delivery. (October 2018) - Zhang, Yu; He, Pan; Liu, Xinming; Zhang, Hongyu; Yang, Huailin; Xiao, Chunsheng; Chen, Xuesi
Graphical abstract: Highlights: A PEGylated alternating copolymer bearing thioether pendants was synthesized by ROAP. The copolymer can self-assemble into stable micelles in water, while disassemble in the presence of H2 O2 . The copolymer was promising for use as oxidation responsive drug delivery nanocarriers. This work highlights the potential use of alternating copolymer for stimuli-responsive drug delivery. Abstract: Synthetic polymers that can change their physicochemical properties in response to physiological stimuli have attracted particular interest for constructing smart drug delivery systems. In the present work, a novel oxidation-responsive block copolymer bearing thioether pendants was designed and synthesized by ring-opening alternating copolymerization (ROAP) of phthalic anhydride (PA) and 2-(methylthio)ethyl glycidyl ether (MTG) monomer using mPEG-OH as the macroinitiator and a phosphazene base, t -BuP1, as the catalyst. The obtained mPEG- b -P(PA- alt -MTG) copolymer could self-assemble into spherical micelles in water with an average size of about 30 nm and a critical micelle concentration value of 7.44 × 10 −3 mg/mL. 1 H NMR results indicated that the hydrophobic thioether group can be selectively oxidized to hydrophilic sulfoxide by H2 O2, leading to disassociation of the micelles as illustrated by the TEM observation. Nile Red, as a model drug, was loaded into the copolymer micelles. The intensity of the fluorescence emission decreased sharply after addition of H2 O2, indicating an oxidation-triggered drug release. Moreover, the drug-loaded micelles could be effectively internalized into MCF-7 cells, as indicated by the confocal laser scanning microscopy (CLSM) and flow cytometry (FCM) studies. MTT assay further demonstrated that the synthesized copolymer showed good biocompatibility towards L929 cell, even at a concentration up to 0.5 mg/mL. In sum, this kind of copolymer may have great potential applications in oxidation responsive drug delivery.